MANAJEMEN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM UPAYA MEMBENTUK BUDAYA RELIGIUS SISWA - Innarotul A'yun; Siti Nurjanah (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2019)
The research is motivated by the teacher's role in Islamic religious education in instilling religious values ​​to students these days are less successful. Education is the process of formality in the classroom. This led to the planting values ​​considered important, especially in shaping religious culture. Religious culture can be formed as a result of the cultivation of religious values. Research methods, this study used a qualitative approach with multi-case. The results after an analysis (1) In planning learning Islamic education covers many things, among others, are making the RPP, the academic calendar, promissory notes, prota. 2) In the implementation of Islamic religious education teaching methods PAKEM; 3) Evaluation of learning Islamic education include daily evaluations, daily tests, replicates mid semester and final exams.